Influence of Tax Knowledge and Awareness on Tax Compliance Among Investors in the Export Processing Zones in Kenya (International Journal of Scientific Research and Management (IJSRM), 2018)
The objective of this study was to examine the influence of tax knowledge & awareness on tax compliance among Export Processing Zones investors in Kenya. This research used a cross sectional survey research design. The study population comprised of 152 duly registered and licensed firms by the Export Processing Zones Authority. Since all the registered investors in the three Kenyan Cities were considered for the study, a census sampling technique was employed. Primary data was gathered using structured questionnaires and captured through a 5-point type Likert Scale questionnaire. Statistical Package for Social Sciences (SPSS) was used in the analysis of data. Data was analyzed by use of descriptive and inferential statistics. Analysis of Variance (ANOVA), multiple regression and correlation analysis was carried out to test the hypothesis. The study established that a significant number of organizations put emphasis on employee training geared at improving their tax knowledge and awareness, thus facilitating tax compliance. The study findings revealed that tax knowledge & awareness has a very close relationship with taxpayers’ ability to understand the laws and regulations of taxation, and their ability to comply with them. It was therefore possible to conclude that firms with well-trained employees on tax issues had a high likelihood of complying voluntarily with tax laws and regulations. The study also led to a conclusion that tax knowledge and awareness had a positive and significant relationship with tax compliance. The study recommends that the Revenue Authorities should embark on public awareness campaigns to educate the public and investors on their role and responsibilities in taxation rather than approaching the matter from a legal obligation perspective. This will create a sense of responsibility in compliance rather than fear for non-compliance. Putting in place active customer oriented information desks as well as client feedback mechanisms is also a necessary tool of increasing tax compliance. Further, more robust measures should be adopted in educating the public and investors on the tax issues and policies through regular training programmes, media advertisements, workshops and seminars. Key Words: Tax Compliance, Tax Knowledge & Awareness, Export Processing Zones